PENGARUH MODEL PEMBELAJARAN TAKE AND GIVE TERHADAP HASIL BELAJAR SISWA PADA TEMA 8 DAERAH TEMPAT TINGGALKU PADA SISWA KELAS IV SD N 060919 SUNGGAL - Sola Grasia Purba; Juliana; Patri Janson Silaban; Regina Sipayung; Antonius Remigius Abi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine (1) To determine the process of implementing the take and give learning model in class IV of SD N 060919 Sunggal in the 2024/2025 academic year in the learning activities of fictional stories and forces on objects (2) To determine the learning outcomes of students in the learning activities of fictional stories and forces on objects using the take and give model in class IV of SD N 060919 in the learning activities of fictional stories and forces on objects (3) To determine the effect of the take and give model on the learning outcomes of students in the take and give learning activities in class IV of SD N 060919 Sunggal in the 2024/2025 academic year. The instruments used in this study consisted of questionnaires and test instruments. The population of this study was all class IV of SD N 060919 Sunggal and had 30 students. There is an influence of the take and give learning model on the learning outcomes of students in my residential area with the material of fictional stories and forces on objects in grade IV. It can be seen from the average value of the student's pretest of 62.67 and the average value of the student's posttest of 76.44. Based on the results of the hypothesis test (t-test) with a value of t_count ≥ t_table, namely 6.279 ≥ 2.048 at a significance level of 0.000 0.05. The data can show that Ha is accepted, namely there is an influence between the take and give learning model assisted by song media (X) on student learning outcomes (Y).